Efficacy of Combined Suprachoroidal Stent and Cataract Surgery in Patients With Glaucoma. Issue 8 (August 2020) - Law, Simon K.; Salazar, Diana; Yu, Fei; Giaconi, JoAnn A.; Chen, Angela; Chopra, Vikas; Francis, Brian; Coleman, Anne L.; Lu, Kenneth; Nouri-Mahdavi, Kouros; Tan, James; Caprioli, Joseph
Abstract : Purpose: The purpose of this study was to evaluate the efficacy of intraocular pressure (IOP) control after combined CyPass Micro-Stent implantation and cataract surgery (combined surgery). Methods: All cases of combined surgery performed from February 2017 to July 2018 at Stein and Doheny Eye Institutes were reviewed. The primary outcome was a qualified success with stratified IOP targets based on criteria: final IOP (A) ⩽18 mm Hg and reduction of 20%, (B) ⩽15 mm Hg and reduction of 25%, (C) ⩽12 mm Hg and reduction of 30%. Secondary outcome measures included postoperative IOP and number of medications, complications, additional glaucoma surgery, and postoperative refractive error. Predictive factors for failure were investigated. IOP spike was defined as a postoperative IOP ≥30 or >10 mm Hg increase from preoperative IOP. Results: One hundred forty-one eyes (107 patients) were included. Mean (±SD) preoperative IOP was 15.4±3.4 mm Hg on an average of 2.2±1.1 medications. A statistically significant reduction in IOP and number of medications was seen at 12 months (13.8±4.2 mm Hg, 1.3±1.3 medications, P <0.001). Fifteen eyes (10.6%) had a postoperative IOP spike. Thirteen eyes (9.2%) experienced 17 complications (12.1%). Additional glaucoma surgery was performed in 3 eyes (2 patients). Cumulative success rates at 1 year based on criteria A, B, and C were 42%, 33%, and 28%, respectively. Lower preoperative IOP, greater preoperative medication number, the occurrence of postoperative IOP spike, and non-Caucasian ethnicity were associated with failure. Conclusion: Combined CyPass Micro-Stent implantation and cataract surgery may reduce glaucoma medication burden with a success rate of 28% to 42% at 1 year.